Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1159/000486824
|View full text |Cite
|
Sign up to set email alerts
|

Multiloculated Cavitary Primary Pulmonary Hodgkin Lymphoma: Case Series

Abstract: Primary pulmonary Hodgkin lymphoma (PPHL) is very rare and typically involves the superior portion of the lung. Pulmonary involvement is observed in 15–40% of Hodgkin lymphoma patients. Three such patients who presented with an unusual form of PPHL in radiological studies, i.e., multiloculated cavitary lesions, were admitted to our hospital. These lesions represent a new pathological and radiological feature of PPHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…According to a study of 40 primary lung lymphoma, 1.5-2.4% were primary lung HL [15], while primary lung cHL was still not frequently seen even if in primary lung lymphoma. Previously reported primary lung HL typically involved the superior portions of unilateral lung [4,[16][17][18][19], while bilateral infiltrates of lymphoma were also seen [20]. In our study, 3 primary lung cHL patients had bilateral lung involvement and were identified to be multiple primary and in stage IV.…”
Section: Discussionsupporting
confidence: 52%
“…According to a study of 40 primary lung lymphoma, 1.5-2.4% were primary lung HL [15], while primary lung cHL was still not frequently seen even if in primary lung lymphoma. Previously reported primary lung HL typically involved the superior portions of unilateral lung [4,[16][17][18][19], while bilateral infiltrates of lymphoma were also seen [20]. In our study, 3 primary lung cHL patients had bilateral lung involvement and were identified to be multiple primary and in stage IV.…”
Section: Discussionsupporting
confidence: 52%
“…Among the reported cases of HL with pulmonary involvement, the typical manifestation involves singular or multiple nodules or masses and primarily involves the superior portion of the lung [2,7] . Cavitary lung lesions, particularly multiloculated, are often associated with alternative etiologies such as mycobacterium tuberculosis (TB), aspergillosis, granulomatosis with polyangiitis, sarcoidosis, and rheumatic nodules [8] .…”
Section: Discussionmentioning
confidence: 99%
“…A patient affected by pulmonary neoplasm is often debilitated with impaired cardiorespiratory function and frequently it is not possible to get tissue samples to achieve a comprehensive diagnosis. Primary pulmonary lymphoma comprises 0.5%‐1% of all primary pulmonary neoplasms and PPHL is a very rarely documented presentation of Hodgkin lymphoma consisting of <1% of all lymphomas and even less among primary pulmonary malignancies . FNA usually allows diagnostic material to be obtained from thoracic masses, which usually prevents the single major rare complication of pneumothorax .…”
Section: Discussionmentioning
confidence: 99%